Throw-rate variations within linkage zones during the growth of normal faults: Case studies from the Western Volcanic Zone, Iceland. (April 2020) - Iezzi, Francesco; Roberts, Gerald; Faure Walker, Joanna
Abstract: This work investigates how throw-rates vary within fault bends and sites of fault linkage during the process of normal fault growth. In the Western Volcanic Zone, Iceland, through detailed field mapping and field measurements of fault throws, normal faults are mapped and along-strike throw profiles are constructed in order to understand how the throw-rates relate with the local fault geometry along faults at different stages of linkage. The results show that throw-rates increase within linkage zones and propagating fault bends independently from the stage of maturity of the fault bend. This implies that 1) the relationship between the local fault geometry and the along-strike distribution of throw-rate is driven by the deeper part of the fault, where established fault bends start propagating to the surface; 2) faults grow first by linkage and coalescence of separate faults, and then by accumulation of slip on the resultant fault, in agreement with models of fault growth by linkage and coalescence; 3) incipient fault bends can produce uncertainty associated with palaeoseismological results, if fault bends remain unrecognised. Moreover, this work demonstrates that existing models showing increased co-seismic and throw-rates within fault bends and sites of fault linkage found in continental extensional settings are valid in a geodynamic context of a mid-oceanic rifts. Highlights: Throw-rates increase within fault bends independently to the stage of maturity of the bend. The relationship between the local fault geometry and throw-rates might be driven from the deeper part of the fault. The growth of normal faults works first to establish the fault length, and then by accumulation of slip. If incipient fault bends are ignored, palaeoseismological studies might be biased. Throw-rates variation in response to the non-planar fault geometry occur also in a mid-oceanic rift.